2023
DOI: 10.3390/tropicalmed8070374
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Staphylococcus aureus Complex Isolated from Free-Ranging Long-Tailed Macaques at Kosumpee Forest Park, Maha Sarakham, Thailand

Abstract: The Staphylococcus (S.) aureus complex, including methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA), and S. argenteus are bacterial pathogens that are responsible for both human and animal infection. However, insights into the molecular characteristics of MRSA, MSSA, and S. argenteus carriages in wildlife, especially in long-tailed macaques, rarely have been reported in Thailand. The objective of this study was to assess molecular characterization of MRSA, MSSA, and S. argente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Staphylococcus aureus is an opportunistic bacterial pathogen posing a zoonotic risk since it can spread among environments, humans and various animals, such as pets, livestock, fish and wildlife (Soliman et al, 2019). A number of studies have reported that S. aureus isolated from non-human primates had close similarity with human isolates, leading to the concern of amphixenoses or zoonotic diseases (Pumipuntu et al, 2023). Therefore, asymptomatic workers and food handlers may constitute a reservoir of virulent strains of S. aureus and may be vectors of their transmission to food via manual contact or through respiratory secretions, thus becoming the source of staphylococcal food poisoning (Hassanain et al, 2013; Elfadaly et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is an opportunistic bacterial pathogen posing a zoonotic risk since it can spread among environments, humans and various animals, such as pets, livestock, fish and wildlife (Soliman et al, 2019). A number of studies have reported that S. aureus isolated from non-human primates had close similarity with human isolates, leading to the concern of amphixenoses or zoonotic diseases (Pumipuntu et al, 2023). Therefore, asymptomatic workers and food handlers may constitute a reservoir of virulent strains of S. aureus and may be vectors of their transmission to food via manual contact or through respiratory secretions, thus becoming the source of staphylococcal food poisoning (Hassanain et al, 2013; Elfadaly et al, 2018).…”
Section: Introductionmentioning
confidence: 99%